ACCOUNTING LABORATORIES IN COLLEGIATE SCHOOLS OF BUSINESS. - Hufford, Kenneth W. (The Accounting Review, 1939)
This article provides guidelines for improving the standard for accountancy laboratories in collegiate schools of business in the U.S. There is frequent and often justified complaint from businessmen that graduates of professional business departments in some of our universities and colleges do not possess the ability to keep a simple set of books. After spending from two to five years in one of these business departments, a graduate may experience a serious setback in confidence if he fails on his first job. No matter where a man finds himself located in the business field, a knowledge of accounting theory will be valuable. However, it requires more than mere "book learning" to understand accounting. In this work one must learn to do by doing. Such is the purpose behind the accounting laboratory method as used in most of our professional schools of business. Equipment is an important element of an efficient accounting laboratory. The present study shows that tables are most satisfactory for problem and practice-set work. A properly equipped laboratory should contain enough steel files or lockers for the purpose of filing completed problems and working materials. In a compulsory system no work is accepted if done away from the workroom, and both finished and unfinished problem material is filed under each student's name.